1995
DOI: 10.3109/00365529509101593
|View full text |Cite
|
Sign up to set email alerts
|

Non-Bleeding Visible Vessel Treatment: Perendoscopic Injection Therapy versus Omeprazole Infusion

Abstract: Our data suggest that omeprazole infusion is a valid alternative to injection treatment of non-bleeding visible vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
3

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 8 publications
0
19
0
3
Order By: Relevance
“…The frequency of rebleeding from nonbleeding visible vessels in patients undergoing "standard medical therapy" (i.e., intravenous H 2 -receptor antagonists and later oral proton pump inhibitors) ranges from 40 to 50%, with 95% confidence intervals from pooled data ranging from 27 to 52% (1,36,38). As previously mentioned, Khuroo et al showed in a post hoc subgroup analysis that 40 mg of oral omeprazole twice daily alone reduced the rebleeding rate of ulcers with nonbleeding visible vessels to 11.8% (20), which is comparable to the rebleeding rate of 17 to 19% achieved by endoscopy alone (39,40). Grosso et al directly compared the two therapies in 42 patients with nonbleeding visible vessels in peptic ulcers randomized to endoscopic injection therapy and standard medical therapy (which included intermittent intravenous ranitidine) or intravenous omeprazole (40 mg twice daily for 2 days) followed by oral omeprazole at 40 mg daily (40).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The frequency of rebleeding from nonbleeding visible vessels in patients undergoing "standard medical therapy" (i.e., intravenous H 2 -receptor antagonists and later oral proton pump inhibitors) ranges from 40 to 50%, with 95% confidence intervals from pooled data ranging from 27 to 52% (1,36,38). As previously mentioned, Khuroo et al showed in a post hoc subgroup analysis that 40 mg of oral omeprazole twice daily alone reduced the rebleeding rate of ulcers with nonbleeding visible vessels to 11.8% (20), which is comparable to the rebleeding rate of 17 to 19% achieved by endoscopy alone (39,40). Grosso et al directly compared the two therapies in 42 patients with nonbleeding visible vessels in peptic ulcers randomized to endoscopic injection therapy and standard medical therapy (which included intermittent intravenous ranitidine) or intravenous omeprazole (40 mg twice daily for 2 days) followed by oral omeprazole at 40 mg daily (40).…”
Section: Discussionmentioning
confidence: 50%
“…As previously mentioned, Khuroo et al showed in a post hoc subgroup analysis that 40 mg of oral omeprazole twice daily alone reduced the rebleeding rate of ulcers with nonbleeding visible vessels to 11.8% (20), which is comparable to the rebleeding rate of 17 to 19% achieved by endoscopy alone (39,40). Grosso et al directly compared the two therapies in 42 patients with nonbleeding visible vessels in peptic ulcers randomized to endoscopic injection therapy and standard medical therapy (which included intermittent intravenous ranitidine) or intravenous omeprazole (40 mg twice daily for 2 days) followed by oral omeprazole at 40 mg daily (40). The rebleeding rate at 48 hr was 19% in both groups.…”
Section: Discussionmentioning
confidence: 51%
“…Grosso et al [63] conducted a European RCT of 42 similar, the 3-week mortality rate in the OME group was comparable to that seen in other studies but was patients with a history of acute bleed and nonbleeding visible vessel and endoscopy within 3 h (endoscopic treat-significantly greater than the unexpectedly low mortality rate seen in the placebo group [65]. Mortality rates in the ment group only).…”
Section: Role Of Ppi Therapy For Ugibmentioning
confidence: 68%
“…[54]. However, as with all retrospective analyses, the results of this study should be interpreted with caution, as Finally, a small randomized trial compared IV OME to endoscopic treatment plus IV RAN, and no significant the different patient groups may not be entirely comparable with regard to clinical characteristics that might differences were noted, but the trial was small and lacked statistical power [63]. affect outcomes of bleeding.…”
Section: Role Of Ppi Therapy For Ugibmentioning
confidence: 98%
“…By contrast, some studies disagree with the primary use of endoscopy in cases with visible vessels or adherent blood clots. Among the pharmacologic agents, administration of PPIs only had an effect comparable to that of endoscopic therapy [13,14].…”
Section: Introductionmentioning
confidence: 96%